Analysis of Supraglottic Activity during Vocalization in Flamenco Singers. - Hermoso, Irene; Rodriguez, Miguel; Quezada, Camilo; Guzmán, Marco (Folia Phoniatrica et Logopaedica, 2025)
Introduction: Flamenco is a traditional music originally from Andalusia in southern Spain. Some of the vocal resources used in Flamenco have components of voice distortion and other voice qualities that could sound like hyperfunctional voice productions. The present study aimed at observing supraglottic activity in flamenco singers while engaged in singing at various degrees of pitch and loudness and while engaged in realizing phonatory tasks. Methods: A total of eighteen flamenco singers with at least 5 years of voice training were recruited. Flexible endoscopic voice evaluations were recorded and edited to provide samples of different pitches, loudness levels, and phonatory tasks. Sound was removed from video samples. Two blinded laryngologists were asked to assess antero-posterior compression, medial compression, pharyngeal compression, and VLP for every sample, using a visual analog scale. Results: Significantly higher values were found for medial compression, anterior-posterior compression, VLP and pharyngeal compression during high loudness levels when compared to medium and low loudness. Overall, medial compression was lower than anterior-posterior compression. Conclusion: Supraglottic activity is present in flamenco singing in the four laryngoscopic variables. It seems to be that supraglottic activity increases with loudness level and pitch. This behavior could be a natural and necessary aspect of flamenco singing present during both sustained vowels and song.